Chess rumble - Neri, Greg (Lee & Low Books, 2007)
A story in free verse poetry in which Marcus, a boy from the inner city who suffers bullying, is grieving his sister's death, and has been labeled a troublemaker finds a way to cope with his anger with the help of an unlikely mentor, who teaches him to play chess.